Chronotopos - Eine Einladung - Schippel, Larisa; Richter, Julia; Rozmyslowicz, Tomasz; Kremmel, Stefanie; Brandtner, Joana; Spitzl, Karlheinz (chronotopos – A Journal of Translation History, 2019)
kein Abstract verfügbar